Polarization effect of quantitative phase imaging using digital holography method - Gasosoth, T.; Jongjinakool, K.; Buranasiri, P. (My University, 2019)
In this study, we investigate polarization effect of quantitative phase imaging (QPI) using digital holography (DH) technique. By using different polarization state of writing beam the reconstructed images of different kinds of samples including biological cells from DH interferometer have been analyzed and shown their difference of quantitative measurement with reconstructed images of unpolarized writing fields. In addition, the property changes of some samples have been studied using the property analysis of the polarization image fields.
Keywords: Biological cells; Digital holography; Polarization; Quantitative phase